The Application of citric acid solutions for selective removal of zinc from steelmaking dust - Krzysztof Gargul; Piotr Handzlik; Piotr Palimąka; Arkadiusz Pawlik (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
Steelmaking dust is one of the wastes which are produced by ironworks. This kind of waste is a byproduct made mainly in electric arc furnace. Zinc content in dust is different and depends on the charge processed in the furnace. The basic technology used for recycling steelmaking dust is Waelz process however it requires a large amount of reducer and generates a lot of waste which need to be stored. First stage in this study was to analyze if steelmaking dust is safe to be exposed for atmospheric conditions. To verify this subject the dust exposed for two kinds of leaching, in standards of TCLP and EN-12457-2. The amount of extracted elements was too large that's why steelmaking dust must be treated as dangerous waste. Leaching in citric acid solutions was divided in four series. The first one was set to determine the time and temperature for most selective zinc leaching. Next series optimized three leaching parameters which were: citric acid concentration, liquid to solid phase ratio (l/s), and the stirring speed. Performed experiments showed the optimal conditions for selective leaching: temperature of 50 °C, leaching time of 60 minutes, citric acid concentration of 0.5 mol/dm3, l/s ratio of 10, and stirring speed of 250 rpm.